2012
DOI: 10.1208/s12249-012-9874-4
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Polymer Biodegradation of Risperidone Poly(d, l-Lactide-Co-Glycolide) Microspheres

Abstract: Abstract. The influence of a tertiary amine, namely risperidone (pKa07.9) on the degradation of poly(D, L lactide-co-glycolide) (PLGA) microspheres was elucidated. Risperidone and blank microspheres were fabricated at two lactide/glycolide ratios, 65:35 and 85:15. The microspheres were characterized for drug loading by high-performance liquid chromatography, particle size by laser diffractometry, and surface morphology by scanning electron microscopy. Polymer degradation studies were carried out with drugloade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…However, the molecular weight of these microspheres exponentially decreased in the presence of risperidone (Fig. 1B), indicating much faster polymer degradation, which was consistent with previous literature reports Selmin et al, 2012).…”
Section: In Vitro Degradation Of Risperidone Microspheressupporting
confidence: 91%
See 1 more Smart Citation
“…However, the molecular weight of these microspheres exponentially decreased in the presence of risperidone (Fig. 1B), indicating much faster polymer degradation, which was consistent with previous literature reports Selmin et al, 2012).…”
Section: In Vitro Degradation Of Risperidone Microspheressupporting
confidence: 91%
“…Risperidone, a tertiary amine drug with a pKa of 8.18 (20°C), has been shown to catalyze PLGA hydrolysis and degradation, thus resulting in a dramatic decrease in polymer molecular weight (Fig. 1) Selmin et al, 2012). Since the prepared risperidone microspheres were similar in composition, critical physicochemical properties of the microspheres may be mainly responsible for the different rates of microsphere degradation and drug diffusion and thereby the different in vitro release characteristics were observed.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the basic nature of drugs can increase PLGA-based DDSs degradation due to their hydrolytic capability, leading to the breakage of ester bonds in the copolymer chain. [143] Beyond the acid-basic behavior of drugs, their solubility and molecular weight are also important factors affecting drug release. [34,144] According to the composition of PLGA, the hydrophilic/hydrophobic ratio of the polymer is variable and may lead to different solubility values and, consequently, to different release profiles.…”
Section: Drug Release From Poly(lactic-co-glycolic) Acid Delivery Sysmentioning
confidence: 99%
“…Bindu et al have reported a UPLC method for quantitating six impurities of paliperidone (9-hydroxy resperidone) in 8 min [7]. Nejedly et al developed a UHPLC method for discrimination the main degradation impurities from risperidone tablet [8]. The new UHPLC method has reduced 4 times of total analysis time comparing with original pharmacopoeial HPLC method.…”
Section: Introductionmentioning
confidence: 99%